Fabrication of SiC-on-Insulator (SiCOI) Layers by Chemical Vapor Deposition of 3C-SiC on Si-in-Insulator Substrates at Low Deposition Temperatures of 1120 °C - Steiner, Johannes; Schultheiß, Jana; Wang, Shouzhong; Wellmann, Peter (Crystals, 2023)
Compared to bulk silicon carbide (SiC) wafers, SiC-on-insulator (SiCOI) substrates enable new device designs of electronic switches as well as novel photonic applications. One application is a micro-resonator for the usage in a Kerr frequency comb. For SiCOI substrates, a deposition temperature below 1200 °C is advisable due to stability reasons of the buried oxide layer during chemical vapor deposition (CVD) process conditions. To create 3C-SiC-on-insulator layers, a cold-wall CVD reactor was utilized, with propane and silane as the sources for carbon and silicon, respectively. To improve the cracking of the carbon source gas at low temperatures, the inner setup of the utilized cold-wall CVD reactor was changed to a non-water-cooled system. The change of the inner reactor setup was investigated numerically, and the grown epitaxial layers were characterized by Raman, EDX, SEM-imaging and XRD spectroscopy. We demonstrate successful deposition of 3C-SiC epitaxial layer substrates at temperatures below 1200 °C without delamination on SOI.
CRIS-Team Scopus Importer:2023-12-08
Keywords: chemical vapor deposition; COMSOL Multiphysics; cubic silicon carbide; photonic applications; silicon-on-insulator